2016
DOI: 10.1007/s00204-016-1879-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and methylomics of CD4-positive T cells in arsenic-exposed women

Abstract: Arsenic, a carcinogen with immunotoxic effects, is a common contaminant of drinking water and certain food worldwide. We hypothesized that chronic arsenic exposure alters gene expression, potentially by altering DNA methylation of genes encoding central components of the immune system. We therefore analyzed the transcriptomes (by RNA sequencing) and methylomes (by target-enrichment next-generation sequencing) of primary CD4-positive T cells from matched groups of four women each in the Argentinean Andes, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…For example, inorganic arsenic (iAs) is a relatively well-studded environmental pollutant present in water and certain food in specific geological regions and exposure to arsenic is a risk factor for different types of cancers as well as cardiovascular and lung diseases [27]. We have shown that exposure to this pollutant induced methylation changes in CD4 + cells that can potentially affect the immune system [28]. Others showed significant associations between genespecific methylation changes in the DNA from blood cells and arsenic exposure [29].…”
Section: Risk Assessment Biomarkersmentioning
confidence: 99%
“…For example, inorganic arsenic (iAs) is a relatively well-studded environmental pollutant present in water and certain food in specific geological regions and exposure to arsenic is a risk factor for different types of cancers as well as cardiovascular and lung diseases [27]. We have shown that exposure to this pollutant induced methylation changes in CD4 + cells that can potentially affect the immune system [28]. Others showed significant associations between genespecific methylation changes in the DNA from blood cells and arsenic exposure [29].…”
Section: Risk Assessment Biomarkersmentioning
confidence: 99%
“…DNA methylation has a high plasticity in utero, making embryogenesis a particularly susceptible window for epigenetic alterations that can alter disease susceptibility later in life (Hochberg et al 2011). In general, the correlation between DNA methylation and gene expression of nearby genes in studies focused on As was reported to be low (Boellmann et al 2010; Engstrom et al 2017; Rojas et al 2015). However, changes in DNA methylation could have a permissive role in regulating gene expression by, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, low CD4 + population in splenic lymphocytes was reported following 30 days exposure of 1 ppm arsenic to male CD57BL6N mice 21 . Therefore, the differential response of CD4 + cells may be due to either dose difference or species specificity 21 , 35 , 36 .…”
Section: Discussionmentioning
confidence: 99%